THE KOLLIKER-FUSE NUCLEUS ACTS AS A TIMEKEEPER FOR LATE-EXPIRATORY ABDOMINAL ACTIVITY - Jenkin, Sarah E. M. (2017)
While the transition from the inspiratory to the post-inspiratory (post-I) phase is dependent on the pons, little attention has been paid to understanding the role of the pontine respiratory nuclei, specifically the Kolliker Fuse nucleus (KF), in transitioning from post-I to the late expiratory (late-E) activity seen with elevated respiratory drive. To elucidate this, we used the in situ working heartbrainstem preparation of juvenile male Holtzman rats and recorded from the vagus (cVN), phrenic (PN) and abdominal nerves (AbN) during baseline conditions and during chemorefiex activation [with potassium cyanide (KCN; n = 13) or hypercapnia (8% CO2; n = 10)] to recruit active expiration. Chemoreflex activation with KCN increased PN frequency and cVN post-I and AbN activities. The inhibition of KF with isoguvacine microinjections (10 mM) attenuated the typical increase in PN frequency and cVN post-I activity, and amplified the AbN response. During hypercapnia, AbN late-E activity emerged in association with a significant reduction in expiratory time. KF inhibition during hypercapnia significantly decreased PN frequency and reduced the duration and amplitude of post-I cVN activity, while the onset of the AbN late-E bursts occurred significantly earlier. Our data reveal a negative relationship between KF-induced post-I and AbN late-E activities, suggesting that the KF coordinates the transition between post-I to late-E activity during conditions of elevated respiratory drive. (C) 2017 IBRO. Published by Elsevier Ltd. All rights reserved.